Occupational stress: analysis of the scientific production in SciELO and BVS-Psi (Fractal: Journal of Psychology, 2009)
The present study had the objective of analysis the article production related to stress. For this such a way, it was proceeded a search in electronic databases (SciELO and BVS-Psi), using the keywords stress, labor stress, occupational stress and psychological assessments. 96 articles were selected, and were analyzed by the year of publication, sex of the author, theoretical review and the used instruments. The summaries majority was relate to psychology magazines, however, had been found articles in magazines of Education, Medicine, Nursing, amongst others. The results had indicated that most of the summaries were referring to the research, being that the main subject was the symptoms survey. In relation to the publication were found a concentration in Estudos de Psicologia (Campinas) and Psicologia Reflexão e Crítica. Besides that, were noticed a increase in the scientific production above the year of 1999.